Disseminated tumor cells in bone marrow as predictive classifiers for small cell lung cancer patients - Ying Wang; Jingying Nong; Baohua Lu; Yuan Gao; Mingming Hu; Cen Chen; Lina Zhang; Jinjing Tan; Xiaomei Yang; Peter Ping Lin; Xingsheng Hu; Tongmei Zhang (Journal of the National Cancer Center)
Background: Small cell lung cancer (SCLC) is a highly aggressive disease characterized by early metastasis. Aneuploid CD31- disseminated tumor cells (DTCs) and CD31+ disseminated tumor endothelial cells (DTECs) residing in the bone marrow are generally considered as the initiators of metastatic process. However, the clinical significance of DTCs and DTECs in SCLC remains poorly understood. The aim of this study is to investigate the clinical implications of diverse subtypes of highly heterogeneous DTCs and DTECs in SCLC patients. Methods: Subtraction enrichment and immunostaining-fluorescence in situ hybridization (SE-iFISH) was applied to enrich and perform comprehensive morphologic, karyotypic, and phenotypic characterization of aneuploid DTCs and DTECs in 30 patients. Additionally, co-detection of circulating tumor cells (CTCs) and circulating tumor endothelial cells (CTECs) was conducted on 24 of the enrolled patients. Proof-of-concept of the whole exon sequencings (WES) on precisely selected different subtypes of CTCs or DTCs, longitudinally detected from a representative case with pathologically confirmed bone marrow metastasis, was validated to feasibly reveal genetic mutations in these cells. Results: DTCs, DTECs and their subtypes were readily detectable in SCLC patients. Comparative analysis revealed that the number of DTCs and DTECs was significantly higher than that of their corresponding CTCs and CTECs (P < 0.001 for both). Positive detection of disseminated tumor microemboli (DTM) or disseminated tumor endothelial microemboli (DTEM) was associated with inferior survival outcomes (P = 0.046 and P = 0.048). Patients with EpCAM+ DTCs detectable displayed significantly lower disease control rate (DCR) (16.67% vs 73.33%, P = 0.019), reduced median progression-free survival (mPFS) and median overall survival (mOS) compared with those with EpCAM- DTCs (P = 0.028 and P = 0.002, respectively). WES analysis indicated that post-treatment DTCs isolated from bone marrow at the time of disease progression shared more homologous somatic gene mutations with pre-treatment CTCs compared with post-treatment CTCs. Conclusions: Our findings suggest that bone marrow sampling and characterization of DTC subtypes provided a valuable tool for predicting treatment response and the prognosis in SCLC. Moreover, DTCs inherit a greater amount of homologous somatic information from pre-treatment CTCs, indicating their potential role in disease progression and treatment resistance.